Health Promotion Interventions Targeting Refugees Resettling in Major Resettlement Countries. A Scoping Review - Shujie Chen; Farzana Yeasmin; Hai Phung; Nicola Wiseman (Journal of Primary Care & Community Health, 2026)
Background & Objectives With the global increase in refugee displacement, countries such as Australia, Canada, and Germany continue to resettle the largest numbers of refugees. Resettled refugees face complex health challenges, including trauma recovery, mental distress, and barriers to healthcare access. Delivering effective health interventions is a critical public health priority. This scoping review examines recent health promotion interventions targeting refugee-background people in major resettlement countries: Australia, Canada, Germany, the US, and Sweden. It seeks to identify the scope of recent focus and the characteristics associated with intervention effectiveness. Methods Following the PRISMA guideline, seven databases were searched for studies published between 2020 and 2024. Data on study design, intervention types, and outcomes were extracted and synthesised narratively. Synthesis Thirty-three studies met the inclusion criteria. Mental health was the predominant focus (20 studies), followed by health literacy (6), social determinants (4), physical activity (3), maternal and infant health (2), and chronic pain (1). Effective interventions consistently featured community engagement, cultural sensitivity, and strong cross-sector collaboration, alongside engaging activities and accessible, safe environments. Applying the socioecological framework, this review also identified an overrepresentation of operating at individual level among recent refugee-targeted health interventions. Conclusion Mental health emerged as the prioritised focus of refugee health interventions in major resettlement countries. However, this review identified a limited number of interventions that operate at socioecological levels beyond the individual level. Strategies that foster trust, safety, engaging activities, cultural relevance, program sustainability, and collaborative partnerships are essential for intervention success. Future research could employ robust designs and objective measures to strengthen evidence and inform scalable models for refugee health equity.